A Study Of The Relationship Between Organizational Culture And Job Performance In A Motor Vehicle Company - Lim, Jia Yu (Universiti Malaysia Sarawak (UNIMAS), 2020)
Organizational culture is the shared believes and values that practiced by the members of organization. It will influence the performance and behavior of organization in achieving organizational goals and development. Hence, organizational culture is a critical and important factor in an organization. There are many compositions include in the organizational culture and this study focuses on a few components such as communication, organizational norms, compensation, training and development and equity which may affects performance. The main objective of this study is to study the relationship between organizational culture and job performance. This study conducted in motor vehicle firms which located at Kuching, Malaysia. There are 100 respondents selected by using random sampling. Quantitative method was used in the study. Questionnaires were distributed to respondents to collect data. The data collected were analyzed using Statistical Package for Social Science (SPSS) version 21. The relationship between organizational culture and performance were examined by using Pearson correlation. The results were recorded and discussed.